2015
DOI: 10.11622/smedj.2015063
|View full text |Cite
|
Sign up to set email alerts
|

An unusual cause of haemorrhagic shock from a subcutaneous haematoma: a Morel-Lavallée lesion

Abstract: A 20-year-old man presented to our emergency department after he was hit by a forklift. He developed haemorrhagic shock from a subcutaneous haematoma in his left thigh and required monitoring in the surgical intensive care unit. He stabilised with aggressive fluid resuscitation with crystalloids and blood transfusion. The recovery was complicated by an infection of the subcutaneous haematoma. Following open drainage of the infected subcutaneous haematoma, he improved and was discharged. To the best of our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Hefny et al [ 6 ] reported a case of MLS in the flunk treated by percutaneous suction drainage. Mao et al [ 7 ] reported a lesion located at the upper thigh treated by surgical drainage. Yumoto et al [ 8 ] reported a lesion of the lower back.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hefny et al [ 6 ] reported a case of MLS in the flunk treated by percutaneous suction drainage. Mao et al [ 7 ] reported a lesion located at the upper thigh treated by surgical drainage. Yumoto et al [ 8 ] reported a lesion of the lower back.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest conservative treatment based on compressive bandaging and strict surveillance [ 11 ]. While others have described many invasive methods like surgical debridement, surgical drainage or injection of sclerosing agents [ 4 , 7 , 12 ]. In our patient, surgical drainage was adequate in controlling the expansion of the hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Severe MLL can sometimes cause significant blood loss and hemodynamic instability (Mao et al 2015). It is one of the unusual and unexpected causes of hypotensive trauma patient.…”
Section: Discussionmentioning
confidence: 99%
“…The Morel-Lavallee Lesion (MLL) was first described by the French Doctor Maurice Morel-Lavallee in 1863 [1][2][3][4][5]. The blunt trauma or tangential force to the fascia results in tearing of the trans-aponeurotic vessels by the separation of the immobile fascia under the mobile subcutaneous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The blunt trauma or tangential force to the fascia results in tearing of the trans-aponeurotic vessels by the separation of the immobile fascia under the mobile subcutaneous tissue. Thus, a cavity comes into being due to the accumulation of hematomas and lymphocele, including necrotic and damaged skin tissues [1][2][3][4][5][6][7][8][9]. MLL is also referred to as "closed internal degloving injury", "Posttraumatic soft tissue cyst", "Morel-Lavallee extravasation or effusion" and "Chronic expanding hematoma".…”
Section: Introductionmentioning
confidence: 99%